Internet memes as contested cultural capital: The case of 4chan's /b/ board. (April 2017) - Nissenbaum, Asaf; Shifman, Limor
This article explores the workings of memes as cultural capital in web-based communities. A grounded analysis of 4chan's /b/ board reveals three main formulations of memes as capital, delineating them as subcultural knowledge, unstable equilibriums, and discursive weapons. While the first formulation follows well-documented notions about subcultural knowledge as a basis for boundary work, the latter two focus on the dualities intrinsic to Internet memes. The contradiction between following conventions and supplying innovative content leads to memes' configuration as unstable equilibriums, triggering constant conflict about their "correct" use. Paradoxically, this struggle highlights collective identity, as it keeps shared culture at the center of discussion. Similarly, when memes are used as jabs at the most intense points of arguments, they function simultaneously as signifiers of superior authoritative status and as reminders of common affinity. Thus, the dualities underpinning memes' structure lead to their performance as contested cultural capital.